Redesign Tempat Penyimpanan Sementara Limbah B3 (Sandblasting) pada PT. X di Kecamatan Puloampel Kabupaten Serang-Banten - Agus Ikhsan Muarif; Febrika Pangesti; Ade Ariesmayana (Jurnal Serambi Engineering, 2024)
Industrial development in the province of Banten is increasing rapidly, especially the development of the manufacturing industry, so it is possible that the amount of waste generated will increase, especially hazardous waste. PT X is one of the manufacturing companies that produces hazardous waste, from several types of hazardous waste produced, one of which is hazardous waste of sand ex sand blasting. This study aims to determine the amount of generation, evaluate the TPSL B3 Sand Ex Sand Blasting and redesign the TPSL B3 Sand Ex Sand Blasting in accordance with PERMEN LHK NO. 06 TAHUN 2021. The data analysis technique in this research was carried out using a mixed method, namely evaluation of TPSL B3 Pasir Ex Sand Blasting and redesign of TPSL B3 Pasir Ex Sand Blasting in accordance with PERMEN LHK NO. 06 TAHUN 2021. Based on the results of this study, the company needs to make improvements related to how to store hazardous and toxic waste with jumbo bag packaging, which has been determined by the applicable government regulations related to hazardous waste generated, and the company needs to improve the procedures for storing hazardous and toxic waste and redesign TPSL B3 Sand Ex Sand Blasting in order to properly manage the hazardous waste when stored and in accordance with the applicable regulations.